The half and half man - Chan, Jonathan Wei Sheng (2015)
Singapore has one of the lowest rates of career engagement and emotional fulfilment in the world, and many Singaporeans find themselves negotiating jobs and careers that detract from their original vision, resulting in discontent and fulfilment. The Half and Half Man is a cautionary narrative that illuminates the realities of such a life, and in doing so, encourages viewers and listeners to engage their ambitions in a more active manner. The narrative presents itself in an illustrated, printed childrens’ book, as well as an animated motion graphics film.